Optimally Facing the uncertainty : A brief survey on Reinforcement Learning - Rajeswari, R. Raja; Pethalakshmi, A (International Journal of Computer Sciences and Engineering, 2025)
Reinforcement Learning is a combination of supervised learning and unsupervised learning, the two main streams of Machine Learning .It has many applications in Artificial Intelligence arena. Multi Armed Bandits problem, a classical Reinforcement Learning task employs exploration and exploitation tradeoff. Efficient Bandit Algorithms for solving Bandit problem proides solutions for various problems from Dynamic pricing to online multi class prediction. This research article analyses the elements of Reinforcement learning, mathematical formulation of multi armed Bandits problem and attempts to present a naive RL algorithm for N-Queens problem for an instance of N=4 and concludes with applications of Reinforcement Learning